Russian-language dictionary of terms used in clinical electromyography and ultrasound examination of the neuromuscular system - A. Yu. Smirnova; D. S. Kanshina; E. P. Bogdanova; V. G. Saltykova; M. V. Sinkin; S. S. Nikitin (Нервно-мышечные болезни, 2021)
Modern electrodiagnostics (ED) and ultrasound examination of the neuromuscular system dictates the need to use unified terminology in order to avoid inter-expert variability in describing the results of the study and drawing up a conclusion in accordance with international criteria. The results of a survey of clinical electromyography specialists and the methodology of translation of the latest version of the English-language glossary on electrodiagnostic medicine are presented.The purpose of the publication is to popularize the use of modern nomenclature among the professional community. An anonymous survey was conducted on the use of the most common terms ED. The translation of the latest English-language version of the glossary on ED and ultrasound examination of the neuromuscular system was carried out, followed by editing and discussion by an expert group. 236 people from 68 cities of Russia and neighboring countries took part in the survey. The survey results demonstrated maximum disunity, as well as conservatism in the use of terms. The nomenclature of ED terms was first compiled in 1980 by the American Association of Electromyography and Electrodiagnostics and subsequently regularly revised and supplemented in accordance with new data. The unification of terms is necessary for the standardization of conclusions, multicenter research and scientific publications.